Comparing the Outcomes of Reporting and Trigger Tool Methods to Capture Adverse Events in the Emergency Department. Issue 1 (March 2019) - Lee, Wen-Huei; Zhang, Ewai; Chiang, Charng-Yen; Yen, Yung-Lin; Chen, Ling-Ling; Liu, Mei-Hsiu; Kung, Chia-Te; Hung, Shih-Chiang
Abstract : Background: Little is known about which methods are best for detecting adverse events in the emergency department (ED). Objectives: This study compared the ability of trigger tool and reporting methods to capture adverse events in the ED and investigated the characteristics of the adverse events identified by each. Methods: This 1-year prospective observational cohort study evaluated a monitoring system that combined 2 reporting methods and 5 trigger tool methods to capture adverse events in the ED of an academic medical center. Measurement outcomes included the number, type, and physical impact of the captured adverse events. Results: Among 69, 327 adult nontrauma ED visits, 285 adverse events were identified. Of these adverse events, 77.2% were identified using reporting methods, 26% using trigger tool methods, and 3.2% using both methods. Most patients (81.7%) incurred temporary, minor physical impacts. Of the adverse events that occurred, 86.7% were related to clinical performance. Compared with reporting methods, trigger tool methods had a lower positive predictive rate to identify adverse events (odds ratio [OR], 0.1; 95% confidence interval [CI], 0.09–0.16), a greater proportion of adverse events occurring during the preinterventation and postintervention phases (OR, 17.0; 95% CI, 8.48–34.16), and more cases of severe physical impact or death (OR, 5.4; 95% CI, 2.62–11.10). Conclusions: The reporting methods more effectively captured greater numbers of adverse events, whereas the adverse events captured by the trigger tool methods were more likely to be severe physical impacts. The combined use of the different methods had synergistic benefits for monitoring adverse events in the ED.